Tumor biological markers and skin cancer: Preliminary analysis - Juri, Héctor; Olazábal, Alberto; Silvera, Daniel; Peña, Raquel; Piguet, Francine (Cirugía del Uruguay, 1992)
The author presents the methodology followed at the Reconstructive Surgery Service at Hospital Maciel as regards cutaneous neoplsms. Ever since May 1990 patients with basocellular carcinoma and spinocel/ular are inc/uded in protoco/s from a prospective point of view. Three protocols are included: c/inica/, biological, and histopathological. Their correlation is analysed so as to understand host-tumor re/ation in a better way. The staging proposed by the American Joint Committee on Cancer for skin, eye..:.tids, and /ip tumors is a/so included.